Optimization of Organizational Design as A Strategy to Improve Organizational Performance: Systematic Literature Review - Bambang Gunawan; Nurdiana Hera Nurul Fitri (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This research is a literature study that reviews strategies for improving organizational performance through optimizing organizational design. The articles reviewed are articles that discuss organizational design and organizational performance. The review method used is a systematic literature review. The search for articles begins in 2016 – 2022. All articles sought are in English. Based on the search results obtained 988 articles. After the data inclusion and exclusion process was carried out, 18 potential articles were obtained for in-depth analysis. Based on the results of the synthesis carried out, it can be concluded that the role of organizational design is very visible in improving organizational performance. In addition, organizational design encourages the emergence of organizational innovation which ultimately encourages increased organizational performance.